Respuestas
Respuesta dada por:
2
Respuesta:
Auxilio me desmayo.
5−2x+4x=−x+7x−5
5−2x+4x=−x+7x−5
5+−2x+4x=−x+7x+−5
(−2x+4x)+(5)=(−x+7x)+(−5)
2x+5=6x+−5
2x+5=6x−5
2x+5−6x=6x−5−6x
−4x+5=−5
−4x+5−5=−5−5
−4x=−10
−4x /−4 = −10 /−4
x= 5/ 2
Explicación paso a paso:
Si me das corona porfa.
lilian3448:
ayudame plis con los otros
20−2x=41−5x
20+−2x=41+−5x
−2x+20=−5x+41
−2x+20+5x=−5x+41+5x
3x+20=41
3x+20−20=41−20
3x=21
3x/3=21/3
x=7
Preguntas similares
hace 4 años
hace 4 años
hace 7 años
hace 8 años
hace 8 años